(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In India same drug molecules are sold under different brand names by different pharmaceuticals. To cite an example: there are over hundred and forty brands of omeprazole, aproton pump inhibitor, available in India. How does a doctor select a brand? What are the factors that influence the prescription behavior of the doctor? What is the influence of pharmaceutical marketing on prescription behavior? Knowledge of prescribing behavior of physicians is a prerequisite for successful marketing of pharmaceutical products. Therefore, this study is aimed to explore the pattern of prescription behavior and major factors influencing physicians’ drug prescription behavior in India with focus on General Physicians and Specialists. To persuade the physicians to prescribe their brands pharmaceuticals engage in marketing techniques like giving samples, gifts, sponsoring travel etc. This study explores the influence of pharmaceutical marketing on the prescription practices of doctors in India. In the last few years the relations between the physicians and pharmaceutical companies have received considerable attention (Moynihan, 1996).